Transformasi Social Intelligence Skills Mahasiswa dalam Ekosistem Pembelajaran Hibrida: A Literature Review - Bayani, Faizul; Muhali, Muhali; Hulyadi, Hulyadi (Multi Discere Journal, 2026)
This study aims to map how university students’ social intelligence skills are reshaped and transformed within hybrid learning ecosystems in higher education. The article applies a PRISMA 2020 guided systematic literature review by examining 28 peer-reviewed journal articles selected from approximately 500 initial records published between 2022 and 2026. The literature was identified through Google Scholar, ScienceDirect (Elsevier), MDPI, and ERIC using keywords related to hybrid learning, blended learning, HyFlex, social presence, belonging, social skills, and socio -emotional competence in higher education. The selected studies were analysed through thematic synthesis to identify changing patterns of social competence, enabling factors, barriers, and pedagogical implications. The review shows that social intelligence skills in hybrid learning can no longer be understood merely as face to face interpersonal ability. They increasingly refer to the capacity to read multimodal social cues, build social presence, sustain a sense of belonging, regulate synchronous and asynchronous collaboration, and adapt social behaviour across physical and digital spaces at the same time. The article concludes that strengthening students’ social intelligence skills in hybrid ecosystems requires intentionally designed pedagogies that place meaningful social interaction, relational support, and socio-emotional reflection at the centre of higher education learning experiences.